Optimisation of copper catalyst by the addition of chromium for the chemical vapour deposition growth of monolayer graphene. (December 2015) - Rezvani, Ehsan; Hallam, Toby; McEvoy, Niall; Berner, Nina C.; Duesberg, Georg S.
Abstract: The effect of adding chromium (Cr) to the copper catalyst for chemical vapour deposition growth of graphene is investigated. We observe a suppression of the formation of multilayer islands of graphene in the Cr-rich regions. This is shown with optical microscopy, scanning electron microscopy and scanning Raman spectroscopy. In addition, carbon isotope labelling is employed to elucidate the mechanism by which the formation of multilayer islands is minimised. The use of mixed catalysts is an important step in the optimisation of catalytic growth of graphene.